172 The Mississippi Beef Quality Assurance Program: Certification Demographics from 2015 to 2019. (28th November 2020) - Pittman, Alexandra M; Karisch, Brandi; Huston, Carla
Abstract: The Mississippi Beef Quality Assurance Program (BQA) has been in place since the early 1990s. In 2015, program materials and format were updated to reflect changing needs of clientele. The current program is a combination of in-person presentation with demonstration of tools such as castration equipment, needles, syringes, etc. to supplement the educational materials. Each registered participant receives a manual, tri-fold supplement, cooler, bumper sticker, and certificate upon completion of the certification. After viewing the presentation, participants complete a 14-question exam to test their knowledge of materials important to the BQA program. Upon passing the exam, participants receive certification, which is valid for 3 yr. Certification events are encouraged to include multiple counties, and reach a wide range of producers. In 2015 to 2017, events were specifically scheduled by state coordinators to ensure cattle producers in all areas of the state had the opportunity to attend a nearby program. Events were also held on an as requested basis. At the end of each certification, participants completed an anonymous survey reporting information on demographics and program effectiveness. From 2015 to 2019, there were 1, 734 total certifications through 57 BQA programs provided. At these events, 26 states were represented. From Mississippi, 64 of 82 counties were represented. When describing total number of cattle, the majority of producers reported owning 1 to 50 head (46%) while only 3% reported owning over 1000 head. Producers also listed the total number of acres in pasture, where the majority reporting 1 to 100 acres (32%) and 6% reporting over 1000 acres. When asked to rank economic impacts, most (26%) reported an estimated more than 25 per head benefit due to increased production and marketing. In summary, producers had small number of cattle and acres of pasture but reported large economic benefits to the certification.